Evaluation of microsatellite allelic patterns to DNA fingerprinting in rubber tree clones (Bioscience Journal, 2022)
The rubber tree (Hevea brasiliensis) is native to the Amazon region, and it is widely exploited due to natural rubber produced from latex. There are many clonal varieties, without certification tests. In order to determine a genetic certification, 15 clones were genotyped to identify their genetic pattern. Ten microsatellites were used to determine a subset of alleles exclusive for each genetic profile. The genetic estimates obtained were: number of alleles per locus (N), expected (HE) and observed (HO) heterozygosity, Polymorphic Information Content (PIC) and Discriminatory Power (DP). The number of alleles (N) ranged from five to 14, with an average of 9.2. The HE mean (0.80) was higher than HO (0.60), indicating a selection for homozygotes. The locus informativeness was verified with PIC (0.77) and DP (0.90) means showing high polymorphism. The dendrogram represented the formation of three groups related to geographical origin. Clone MDF 180 presented the highest genetic divergence. Two genic pools represented the genetic composition of genotypes. Based on allelic profiles, a set of two microsatellites (A2365 and A2368) was able to distinguish all examined clones. The genetic certification using microsatellite fingerprinting proved to be an alternative to morphological traits.